Pengaruh Orientasi Pasar Dan Inovasi Strategi Terhadap Kinerja Usaha Mikro Kecil Dan Menengah (UMKM) Pada Masa Covid-19 - Disa Faletina Falentina; R Deni Muhammad Danial; Resa Nurmala (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the description and influence on market orientation, strategic innovation on the performanceof of micro, small and medium enterprises (MSMEs) in the city of Sukabumi during the Covid-19 period. The type of research carried out is quantitative research with a strategic management approach method. The population is fashion MSME in Sukabumi City totaling 38. The data collection technique uses total sampling, which means that the entire population in this study is sampled. Data analysis technique using the validity and reliability test of IBM SPSS version 26for windows. The result of multiple linear regression analysis show that market orientation (X1) and innovation (X2)affect the performance of MSME (Y) indicated by a sig value of more than 0,05 and obtained a t table of 1,68709 so H1 and H0 were rejected, meaning that there was a positive influence on market orientation on the performance of MSME in Sukabumi City. Keywords : market orientation, strategic inovation, MSME